Variation of moisture state and taste characteristics during vacuum drying of Maillard reaction intermediates of hydrolyzed soybean protein and characterization of browning precursors via fluorescence spectroscopy. (December 2022) - Huang, Chen; Cui, Heping; Hayat, Khizar; Zhang, Xiaoming; Ho, Chi-Tang
Graphical abstract: Highlights: Maillard reaction intermediates prepared by vacuum drying showed taste enhancement. Reaction of small peptides with glucose led to a decline in taste enhancement. Fluorescence spectroscopy was a practical means to characterize browning precursors. Abstract: Maillard reaction intermediates (MRIs) derived from enzymatic hydrolysates of soybean protein were prepared by combining dehydration method with spray drying and vacuum drying. Taste characteristics, browning precursors, water activity, and moisture state were monitored during the process of vacuum drying. The water activity was significantly reduced and the proportion of bound water was increased, which could promote the large accumulation of MRIs. The saltiness, umami, and bitterness responses of MRIs were all reduced and the reduction of taste intensity during vacuum drying was probably caused by the reaction of small peptides of taste-active amino acids with glucose. The continuous accumulation of browning precursors during vacuum drying was confirmed by fluorescence spectroscopic analysis and by quantitative analysis of α-dicarbonyl compounds. Subsequent browning reactions further demonstrated that the MRI with the highest fluorescence intensity also had the greatest browning potential.